2015
DOI: 10.3389/fmicb.2015.01243
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Activity of Lysobacter Species from Disease Suppressive Soils

Abstract: The genus Lysobacter includes several species that produce a range of extracellular enzymes and other metabolites with activity against bacteria, fungi, oomycetes, and nematodes. Lysobacter species were found to be more abundant in soil suppressive against the fungal root pathogen Rhizoctonia solani, but their actual role in disease suppression is still unclear. Here, the antifungal and plant growth-promoting activities of 18 Lysobacter strains, including 11 strains from Rhizoctonia-suppressive soils, were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 67 publications
4
74
0
Order By: Relevance
“…Isolate K-Hf-H2 failed to exhibit biocontrol potential during the initial biocontrol assessment in vermiculite. Gómez et al (2015) obtained a similar result in a study conducted to understand the diversity and activity of Lysobacter spp. Such inconsistency could be attributed to the growing medium (i.e., vermiculite), which might have altered the production of inhibitory metabolites by the isolate K-HF-H2 and (or) the isolate might need to interact with other microbes to maintain antagonistic potential against A. euteiches.…”
Section: Bacterial Isolates Mean Diseasesupporting
confidence: 58%
See 1 more Smart Citation
“…Isolate K-Hf-H2 failed to exhibit biocontrol potential during the initial biocontrol assessment in vermiculite. Gómez et al (2015) obtained a similar result in a study conducted to understand the diversity and activity of Lysobacter spp. Such inconsistency could be attributed to the growing medium (i.e., vermiculite), which might have altered the production of inhibitory metabolites by the isolate K-HF-H2 and (or) the isolate might need to interact with other microbes to maintain antagonistic potential against A. euteiches.…”
Section: Bacterial Isolates Mean Diseasesupporting
confidence: 58%
“…Such inconsistency could be attributed to the growing medium (i.e., vermiculite), which might have altered the production of inhibitory metabolites by the isolate K-HF-H2 and (or) the isolate might need to interact with other microbes to maintain antagonistic potential against A. euteiches. Lysobacter are well known to produce various extracellular bioactive molecules, which include enzymes and compounds with antimicrobial activities (Zhang et al 2001;Palumbo et al 2005;Reichenbach 2006;Ko et al 2009;Xie et al 2012;Vasilyeva et al 2014;Gómez et al 2015).…”
Section: Bacterial Isolates Mean Diseasementioning
confidence: 99%
“…Lysobacter spp. may play an important role in the suppression of banana Panama disease since it could produce a wide range of extracellular enzymes and other metabolites with antagonistic activity against many soil‐borne pathogens (Expósito et al ., ). As Bacillus spp.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Gómez Expósito et al . () recently showed that Lysobacter species, although more enriched in Rhizoctonia disease‐suppressive soils and exhibiting strong activity against R. solani in vitro (De Bruijn et al . ), did not provide plant protection against fungal attack.…”
Section: Discussionmentioning
confidence: 99%